2011
DOI: 10.2478/s11535-011-0050-8
|View full text |Cite
|
Sign up to set email alerts
|

Protein glycosylation in infectious disease pathobiology and treatment

Abstract: A host of bacteria and viruses are dependent on O-linked and N-linked glycosylation to perform vital biological functions. Pathogens often have integral proteins that participate in host-cell interactions such as receptor binding and fusion with host membrane. Fusion proteins from a broad range of disparate viruses, such as paramyxovirus, HIV, ebola, and the influenza viruses share a variety of common features that are augmented by glycosylation. Each of these viruses contain multiple glycosylation sites that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 145 publications
(134 reference statements)
0
21
0
Order By: Relevance
“…Several studies have confirmed that glycosylation can significantly influence the structure, function, stability, antigenicity, and immunogenicity of various viral glycoproteins. In addition, it has been demonstrated that in many infections, immune responses are mostly generated against the glycosylated portions of protein (Rudd et al, 2001;Goffard et al, 2005;Dowling et al, 2007;Marth & Grewal, 2008;Vigerust, 2011). The expressed G1 glycoprotein by pcDNA3.1-G1 construct is structurally similar to native protein, thus it may induced considerably the immune responses in the form of DNA vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confirmed that glycosylation can significantly influence the structure, function, stability, antigenicity, and immunogenicity of various viral glycoproteins. In addition, it has been demonstrated that in many infections, immune responses are mostly generated against the glycosylated portions of protein (Rudd et al, 2001;Goffard et al, 2005;Dowling et al, 2007;Marth & Grewal, 2008;Vigerust, 2011). The expressed G1 glycoprotein by pcDNA3.1-G1 construct is structurally similar to native protein, thus it may induced considerably the immune responses in the form of DNA vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the importance of protein glycosylation in biological systems, glycoproteomics has been extensively applied to disease-related research (Whelan et al, 2009;Hwang et al, 2010;Song et al, 2014;Reiding et al, 2017;Yang et al, 2017b;Kailemia et al, 2018), such as hepatitis, cancer (Dai et al, 2011;Liu et al, 2014;Kailemia et al, 2017;Miyamoto et al, 2018;Veillon et al, 2018), and infectious diseases (Vigerust, 2011;Go et al, 2017). Glycosylation can change chemical and physical properties of proteins, and regulate their binding and interactions with ligands or extracellular matrix.…”
Section: E Clinical Samplesmentioning
confidence: 99%
“… 2 8 Aberrant surface protein glycosylation impacts on cellular properties, such as cell solubility and mobility, which are related to human disease, 9 11 including cancer, 12 , 13 congenital disorders and infectious diseases. 14 , 15 It has long been understood that the covalent attachment between glycans and proteins is extremely complicated because of the heterogeneity of glycan structures, which makes the comprehensive analysis of protein glycosylation challenging. 16 – 24 It is even more difficult to analyze glycoproteins located only on the cell surface.…”
Section: Introductionmentioning
confidence: 99%